2004
DOI: 10.3732/ajb.91.6.837
|View full text |Cite
|
Sign up to set email alerts
|

Life‐history variation and adaptation in the historically mobile plant Arabidopsis thaliana (Brassicaceae) in North America

Abstract: We used field-collected seeds of Arabidopsis thaliana (Brassicaceae) to simulate a colonization event of plants from diverse locations into a common environment to compare regionally "local" and "foreign" populations of this historically mobile species. Life history varied among regional groups, but most variation was found among populations within regions. While we found significant differences among populations and regional groups for important life-history characters, we did not find significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 48 publications
3
87
0
Order By: Relevance
“…This study provides, to our knowledge, the first direct field test of regional climate adaptation in A. thaliana, although several previous studies have measured the fitness of natural accessions in the field in this species (26,28,39,41,(46)(47)(48)(49)(50)(51). Reciprocal transplant experiments between northern and southern sites show evidence of local adaptation but were not designed to distinguish the role of climate (41).…”
Section: Discussionmentioning
confidence: 99%
“…This study provides, to our knowledge, the first direct field test of regional climate adaptation in A. thaliana, although several previous studies have measured the fitness of natural accessions in the field in this species (26,28,39,41,(46)(47)(48)(49)(50)(51). Reciprocal transplant experiments between northern and southern sites show evidence of local adaptation but were not designed to distinguish the role of climate (41).…”
Section: Discussionmentioning
confidence: 99%
“…While small amounts of spring germination have been observed in typically winterannual populations of A. thaliana (Baskin and Baskin 1983), populations in New England have been observed to have high frequencies of spring germination, possibly because of their ability to set seeds in the autumn (Griffith et al 2004). We predict therefore that adaptive plastic responses to germination season would evolve most easily in such populations.…”
Section: Natural Selection On Life History and Its Plasticitymentioning
confidence: 99%
“…In KY, germination timing alone accounted for 72% of the variation in fitness among genotypes. Many studies have demonstrated strong natural selection on naturally segregating germination variants (Miller 1987;Kalisz 1989;Biere 1991;Gross and Smith 1991;Masuda and Washitani 1992;Donohue 2002;Griffith et al 2004). This study shows just how strong natural selection on germination timing can be on a range of potential segregants derived from natural genotypes.…”
Section: The Strength Of Natural Selection On Germinationmentioning
confidence: 99%
“…Transgressive segregation after hybridization between distinct lineages creates novel genotypes that can contribute to adaptive evolution and ecological diversification in hybrid species (Lexer et al 2003;Rieseberg et al 2003a,b), and hybridization is also hypothesized to contribute to invasiveness (Ellstrand and Schierenbeck 2000). Hybridization of colonizing lineages and the resulting creation of novel genotypes followed by lineage sorting may be an especially effective process for the rapid creation and subsequent preservation of adaptive gene complexes in selfing species (Weinig et al 2003;Griffith et al 2004). We simulated this sort of dynamic of novel genotypes in novel environments by experimentally creating a set of recombinant inbred lines to measure natural selection on germination timing and other life-history traits in two geographic locations.…”
mentioning
confidence: 99%